A Phase III, randomized, double-blind, placebo-controlled, multicenter study of fruquintinib in Chinese patients with advanced nonsquamous non-small-cell lung cancer – The FALUCA study. (August 2020) - Lu, Shun; Chen, Gongyan; Sun, Yuping; Sun, Sanyuan; Chang, Jianhua; Yao, Yu; Chen, Zhendong; Ye, Feng; Lu, Junguo; Shi, Jianhua; He, Jianxing; Liu, Xiaoqing; et al.
Highlights: Fruquintinib is a highly selective inhibitor of VEGFR. Efficacy and safety of fruquintinib for advanced NSCLC are presented. Although primary endpoint of OS failed, fruquintinib improved PFS, ORR, and DCR. Fruquintinib may be effective in combination with other therapeutic agents. Abstract: Objectives: Fruquintinib is an orally active kinase inhibitor that selectively targets the vascular endothelial growth factor (VEGF) receptor. A Phase II trial has demonstrated a significant benefit in progression-free survival (PFS) for fruquintinib-treated patients with locally advanced/metastatic nonsquamous non-small-cell lung cancer (NSCLC) who have progressed after second-line chemotherapy. This Phase III trial is a randomized, double-blind, multicenter trial to confirm fruquintinib's efficacy in the same patient population. Materials and methods: From December 2015 to February 2018, 730 patients were screened, of whom 527 were enrolled into the study. Participants were randomized 2:1 to receive fruquintinib (n = 354) or placebo (n = 173) once daily for 3 weeks on-treatment, and 1 week off-treatment. Patients were stratified according to epidermal growth factor receptor mutation status and prior use of VEGF inhibitors. Primary endpoint was overall survival (OS). Results: Median OS was 8.9 months for the fruquintinib group and 10.4 months for placebo group (hazard ratio [HR] 1.02; 95 % confidence interval [CI], 0.82–1.28; P  = 0.841), with median PFS of 3.7 months and 1.0 months, respectively (HR 0.34; 95 % CI, 0.28–0.43; P  < 0.001). Objective response rate and disease control rate were 13.8 % and 66.7 % for fruquintinib, and 0.6 % and 24.9 % for placebo, respectively ( P  < 0.001). Hypertension was the most frequent treatment-emergent adverse event (≥grade 3) observed in fruquintinib-treated patients (21.0 %). Post hoc analysis revealed that fruquintinib prolonged the median OS for patients who did not receive subsequent antitumor therapy: 7.0 months versus 5.1 months for placebo (HR 0.65; 95 % CI, 0.46–0.91; P  = 0.012). Patients receiving fruquintinib also reported improvements in quality of life for most functional scales measured by EORTC QLQ-C30 and LC13 questionnaires. Conclusion: Although the study did not meet its primary endpoint, fruquintinib could be effective in combination with other agents for the treatment of patients with NSCLC who have failed second-line chemotherapy.